2007
DOI: 10.1055/s-2007-986695
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Preterm Infants Fed a Formula Containing Long-Chain Polyunsaturated Fatty Acids (LCPUFA)

Abstract: Our study examined if dietary long-chain polyunsaturated fatty acids (LCPUFA) have an impact on oxidative stress in preterm infants. Serum malonyldialdehyde (MDA), total peroxide concentrations, and total antioxidant capacity were determined at mean (standard deviation [SD]) 34.7 (10.9) days of life in 104 healthy preterm infants (gestational age, 32.6 [2.9] weeks; birthweight; 1605 [285] g) who were randomly assigned to be fed since birth either a formula containing LCPUFA (arachidonic and docosahexaenoic) (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The LCPUFA intervention did not have an effect on growth rate. Similar data were described with SMOFLipid, an emulsion based on fish oil including ARA and DHA [42] or with a combination of ARA:DHA similar to the one used in this study [41]. Although we did not detect an improvement in growth, it is possible that this supplementation might reduce perinatal morbidities or improve neurodevelopment, an aspect which should be evaluated in a larger cohort.…”
Section: Effect Of Lcpufa On Infant Growthsupporting
confidence: 77%
See 1 more Smart Citation
“…The LCPUFA intervention did not have an effect on growth rate. Similar data were described with SMOFLipid, an emulsion based on fish oil including ARA and DHA [42] or with a combination of ARA:DHA similar to the one used in this study [41]. Although we did not detect an improvement in growth, it is possible that this supplementation might reduce perinatal morbidities or improve neurodevelopment, an aspect which should be evaluated in a larger cohort.…”
Section: Effect Of Lcpufa On Infant Growthsupporting
confidence: 77%
“…A tendency toward an increase in Antiox-S was observed at day 28, but did not reach statistical significance (p = 0.069). In a study with a similar intervention (ARA:DHA 1.6:1), supplementation for seven days did not modify total antioxidant capacity in preterm neonates [41]. These data suggest that long periods of supplementation might be needed to produce an effect.…”
Section: Effect Of Supplementation On Oxidative Statusmentioning
confidence: 82%
“…In contrast, a study in preterm infants, comparing the effects of formulas with or without LC-PUFA but the same vitamin E content, found a decreased α-tocopherol/total lipid ratio in erythrocytes and lower plasma α-tocopherol contents with LC-PUFA enriched formulas. , Preterm infants are most likely more susceptible to peroxidation, therefore these findings cannot be extrapolated to term infants. Moreover, other studies in preterm infants showed no effect of LC-PUFA enrichment on vitamin E levels or markers of oxidative stress (i.e., total plasma antioxidant capacity (PAC), serum malondialdehyde (MDA), total peroxides and total antioxidant capacity (TAC)). , Interestingly, even antioxidant effects of n-3 fatty acids or LC-PUFA were reported in preterm infants receiving parenteral nutrition enriched with n-3 LC-PUFA plus added vitamin E, compared to a standard soybean-oil-based lipid emulsion or getting LC-PUFA enriched compared to not-enriched formulas. , …”
Section: Introductionmentioning
confidence: 98%
“…Studies on effects of LC-PUFA enriched formulas for term infants on antioxidant status or markers of peroxidation are rare. Most of such studies relate to low-birth-weight or preterm infants, but only a few relate to term infants. Gonzáles-Corbella et al did not find differences in α-tocopherol concentrations and vitamin E/LC-PUFA ratios (mg/%) in plasma and red blood cells in term infants fed human milk, or formulas (with or without LC-PUFA). However, formulas contained higher levels of tocopherol …”
Section: Introductionmentioning
confidence: 98%
“…Exposure to light during tube feeding increases lipid peroxidation in infant formula but not in human milk. It has been observed that supplementing infant formulas with LCPUFA does not affect lipid peroxidation in the plasma of healthy, preterm infants (6). An investigation of the extent to which formula milk and stored breast milk, both commonly used in hospitals, could be pro-oxidant sources for newborn babies, found that there were notable differences in the oxidation parameters of several formula milk brands, particularly concerning the levels of lipid peroxides and total antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%